Research on the construction of the spiral evolutionary design methodology for a product service system based on existing products. (March 2020) - Jiang, Shaofei; Feng, Di; Lu, Chunfu; Li, Jiquan; Chai, Hao
A product service system composed of products, services, hardware and software support, and stakeholders enhances the added value and competitiveness of products through resource integration. To reduce the input in servitization and improve feasibility, manufacturers tend to construct a product service system based on existing products to meet the demands of customers, instead of constructing a completely new product service system. Therefore, this article presents a spiral evolutionary design method to construct a product service system based on existing products. With the ultimate goal of the system evolution being the maximization of the use of existing products while satisfying the demands of customers, the system performance will be spirally upgraded under the guidance of the system evolution chain through the operation of the system symbiotic ring. The construction of a mobile fire extinguishing product service system based on existing fire-fighting equipment was used as an example to illustrate the feasibility of this methodology. Finally, a feasibility evaluation system was established to evaluate and compare the previous product service system methodologies with the methodology in this article.